2010
DOI: 10.1016/j.micinf.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

LipL53, a temperature regulated protein from Leptospira interrogans that binds to extracellular matrix molecules

Abstract: The regulation of gene expression by environmental signals, such as temperature and osmolarity, has been correlated with virulence. In this study, we characterize the protein LipL53 from Leptospira interrogans, previously shown to react with serum sample of individual diagnosed with leptospirosis and to be up-regulated by shift to physiological osmolarity. The recombinant protein was expressed in Escherichia coli system, in insoluble form, recovered by urea solubilization and further refolded by decreasing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 40 publications
2
44
0
13
Order By: Relevance
“…We performed a proteinase K accessibility assay by using a described assay 14,39 with some modifications. Live L. interrogans serovar Copenhageni strain M-20 was treated with 25 μg/mL of proteinase K, and aliquots of the bacterial suspensions were obtained at 0, 30, 60, 120, and 240 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We performed a proteinase K accessibility assay by using a described assay 14,39 with some modifications. Live L. interrogans serovar Copenhageni strain M-20 was treated with 25 μg/mL of proteinase K, and aliquots of the bacterial suspensions were obtained at 0, 30, 60, 120, and 240 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Several laminin-binding proteins were identified, which indicated that leptospires have a redundant repertoire of adhesion molecules that are probably part of their invasion strategies. Lsa23, Lsa26, and Lsa36 bind laminin in a dose-dependent, specific, and saturable manner, fulfilling the properties of receptor-ligand interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins are exposed to hosts and then are potential targets for inducing immune response during infection. In addition, it is possible that some of these membrane proteins mediate the initial adhesion to host cells, as has been reported by several researchers (5,7,13,14,22,23,26,29,37,41,50,55). After adherence, pathogens have to surmount host tissue barriers in order to reach blood circulation and organs.…”
mentioning
confidence: 93%